Identifying strategies for adaptation of rural women to climate variability in water scarce areas - Moayedi, Masoumeh; Hayati, Dariush (Frontiers in Water, 2023)
The current research aims to identify adaptation strategies adopted by rural women of Fars province in dealing with climate variability. This study is applied in terms of purpose, descriptive-correlational in terms of methodology, and field type in terms of data collection. The statistical population were rural women who were members of agricultural households in Fars province, which have been affected by climatic variability in four climatic zones: cold, mild, hot, and very hot. This study was conducted using survey method. A structured questionnaire was designed and its face and content validities were verified using experts' opinions. The size of the studied sample was estimated using Cochran's formula. For sampling, a combined stratified and cluster sampling method was used. Data were collected from 406 respondents from 32 villages in eight counties of Fars province. Then, the data was analyzed. In total, 43 adaptation strategies of rural women were classified in the form of four categories of strategies for development and diversification of income sources, cost management, social capital management, and environmental stress management. The most important adaptation strategy used by rural women against climatic changes has been the cost management strategy. The use of facilities and loans is the most important strategy among the cost management strategies that can lead to reducing the negative effects of climate variability on rural women. Then, the strategy of development and diversification of income sources, management of social capital, and management of environmental tensions were placed in the second to fourth places of adaptation strategies used by rural women under climate variability. The results of this study indicate that the rural women of Fars province are not only passive victims of climate changes, but they act actively and hope to adapt to sudden climate changes. Using prudent strategies, they employ their experience and expertise to reduce the adverse effects of climate variability.